THE EFFECT OF TECHNOLOGY ON THE EXPRESSION AND CONSUMPTION OF ART IN INDONESIA - Nurul Hichmah (Institut Seni Indonesia Padangpanjang, 2024)
Technology has become increasingly prevalent in the art industry in recent decades, fundamentally impacting the way art is produced as well as society's views and values. This article provides a comprehensive overview of how digital technology has transformed traditional art media and enabled new forms of creativity. The article analyzes Ruangrupa as an Indonesian contemporary art collective that utilizes technology in its projects and activities. The article uses literature analysis to provide insights into the opportunities and challenges faced by artists and society in the digital era. The results show that technology affects the way art is created and viewed by society. The article concludes with recommendations on how society and government can support these positive developments and at the same time manage the associated risks. Amidst ever-changing technological innovations, proper support will ensure that art remains an authentic expression of human experience and an important agent of social and cultural change.